How is COVID nursing different? A phenomenological analysis of the nurses’ experience from a tertiary care COVID units - Kaur, Jasleen; Dhandapani, Manju; Kaur, Sukhpal; Venkadalakshmi; Dhandapani, Sivashanmugam; Das, Karobi (International Journal Of Community Medicine And Public Health, 2023)
Healthcare workers face specific challenges during infectious disease outbreak. Along with fear of getting infection, performing new, unfamiliar tasks in unfamiliar setting with new outfit (PPE) complicates their working. We explore perceptions and lived experiences of front-line nurses who cared for COVI9-19 confirmed patients in a tertiary hospital of North India eighteen in-depth, telephonic, semi structured interviews were conducted. Interviews were transcribed and analysed using Colaizzi’s phenomenological method. Nurses were challenged by risk of infection or fear of transmission, working in a new setting, unfamiliar clinical roles, heavy workloads, ineffective communication and discomforts of protective gear. Despite facing various challenges, nurses showed great strength and resilience. Good administrative support, PPE surveillance, developing nurses’ task force with distinct responsibilities, orientation, training and empowerment are suggested strategies to overcome the challenges and enhance the resilience. Nurses lived experiences will be helpful to healthcare organizations preparing for or responding to outbreaks or disaster.